Identifying a Novel Role for Fractalkine (CX3CL1) in Memory CD8+ T Cell Accumulation in the Omentum of Obesity-Associated Cancer Patients - Conroy, Melissa J.; Maher, Stephen G.; Melo, Ashanty M.; Doyle, Suzanne L.; Foley, Emma; Reynolds, John V.; Long, Aideen; Lysaght, Joanne (Frontiers in Immunology, 2018)
The omentum is enriched with pro-inflammatory effector memory CD8+ T cells in patients with the obesity-associated malignancy, esophagogastric adenocarcinoma (EAC) and we have identified the chemokine macrophage inflammatory protein-1alpha (MIP-1α) as a key player in their active migration to this inflamed tissue. More recently, others have established that subsets of memory CD8+ T cells can be classified based on their surface expression of CX3CR1; the specific receptor for the inflammatory chemokine fractalkine. CD8+ T cells expressing intermediate levels (CX3CR1INT) are defined as peripheral memory, those expressing the highest levels (CX3CR1HI) are effector memory/terminally differentiated and those lacking CX3CR1 (CX3CR1NEG) are classified as central memory. To date, the fractalkine:CX3CR1 axis has not been examined in the context of CD8+ T cell enrichment in the omentum and here we examine this chemokines involvement in the accumulation of memory CD8+ T cells in the omentum of EAC patients. Our data show that fractalkine is significantly enriched in the omentum of EAC patients and drives migration of T cells derived from EAC patient blood. Furthermore, CX3CR1 is endocytosed specifically by CD8+ T cells upon encountering fractalkine, which is consistent with the significantly diminished frequencies of CX3CR1INT and CX3CR1HI CD8+ T cells in the fractalkine-rich environment of omentum in EAC, relative to matched blood. Fractalkine-mediated endocytosis of CX3CR1 by CD8+ T cells is sustained and is followed by enhanced surface expression of L-selectin (CD62L). These novel data align with our findings that circulating CX3CR1NEG CD8+ T cells express higher levels of L-selectin than CX3CR1INT CD8+ T cells. This is consistent with previous reports and implicates fractalkine in the conversion of CX3CR1INT CD8+ T cells to a CX3CR1NEG phenotype characterised by alterations in the migratory capacity of these T cells. For the first time, these findings identify fractalkine as a driver of T cell migration to the omentum in EAC and indicate that CD8+ T cells undergo sequenced fractalkine-mediated alterations in CX3CR1 and L-selectin expression. These data implicate fractalkine as more than a chemotactic cytokine in obesity-associated meta-inflammation and reveal a role for this chemokine in the maintenance of the CX3CR1NEG CD8+ T cell populations.